2022
DOI: 10.1080/03019233.2022.2052413
|View full text |Cite
|
Sign up to set email alerts
|

Energy balance between multiple supersonic jets and molten bath in BOF steelmaking

Abstract: A multi-fluid volume of fluid (VOF) model for compressible oxygen flow in a 260t top blown converter was established. The energy transfer efficiency of the top blown gas to the molten pool was analyzed. A user-defined function was used to calculate splash energy consumption. The energy conservation equation of 'jet attenuationcavity formationbath stirringmolten steel splashing' was established. The results show that more than 75% of the total energy is wasted in jet attenuation. The energy used stirring bath a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…∆T BOF = ∆T melt + ∆T add − ∆T Ar − ∆T lining (1) where ∆T BOF is the value of the change in steel temperature during the steel discharge phase of the converter ( The main task of this stage is to remove the carbon, silicon, manganese, phosp sulfur, and oxygen contained in the iron to a certain extent under high-tempe oxidizing conditions and to raise the temperature to that of steel; this essentially in a process of oxidizing the elements in the molten pool by releasing a large amount o…”
Section: Mechanism Analysis Of Bofmentioning
confidence: 99%
See 1 more Smart Citation
“…∆T BOF = ∆T melt + ∆T add − ∆T Ar − ∆T lining (1) where ∆T BOF is the value of the change in steel temperature during the steel discharge phase of the converter ( The main task of this stage is to remove the carbon, silicon, manganese, phosp sulfur, and oxygen contained in the iron to a certain extent under high-tempe oxidizing conditions and to raise the temperature to that of steel; this essentially in a process of oxidizing the elements in the molten pool by releasing a large amount o…”
Section: Mechanism Analysis Of Bofmentioning
confidence: 99%
“…Basic oxygen furnace (BOF) steelmaking is of great importance; it is the main method of the steelmaking process in the thermal cycle of steel. In this process, hot metal and scrap are rapidly refined into liquid steel with the required carbon content by means of a supersonic oxygen injection from the top lance and through stirring from the bottom air outlet [1]. At the same time, melting agents such as lime and dolomite are added to the vessel for processing, and impurities are removed [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Zhou and Ersson et al [7] found that the energy transfer for the bottom blowing is much more efficient than that of the top blowing operations. Liu et al [8] found Metals 2024, 14, 56 2 of 21 that more than 75% of the total energy is wasted in the process of jet attenuation, and the energy used for stirring the bath is less than 1.5% of the total energy. Li et al [9] presented a numerical study of transferring the characteristics of momentum/energy during oxygen jetting into the slag-metal molten bath.…”
Section: Introductionmentioning
confidence: 99%
“…They found that individual particles undergo spreading, retracting, and stabilizing processes when they impact the wall. Liu et al [8] analyzed the energy transfer efficiency of the top-blown gas to the molten pool through numerical simulations. They calculated the energy consumption of the splashing process and established the energy conservation equation in the blowing process.…”
Section: Introductionmentioning
confidence: 99%